GPR40 carboxylic acid receptor family and diabetes: a new drug target - Telvekar, V N; Kundaikar, H S (Current drug targets, 2008)
Type-2 diabetes is strongly linked to visceral obesity and elevated levels of circulating free fatty acids. For years this correlation of obesity to diabetes has intrigued the minds of researchers and research in this direction has led to a possible solution to this question. Human Genome project has identified nearly 150 orphan GPCRs. The reverse pharmacology approaches have identified free fatty acids as ligands for the GPR40 family of orphan receptors. This review mainly emphasizes on the role of GPR40 carboxylic acid receptor family in the development of diabetes along with detailed coverage of each receptor of the family. GPR40 family has provided an insight into regulation of carbohydrate and lipid metabolism in vertebrates and has further provided targets for the development of therapeutic agents useful for treating or preventing disorders such as Type-2 diabetes. This review also suggests where further research and development could be beneficial.